Reforma al artículo 385 del código orgánico integral penal en lo concerniente a la desigualdad de la tolerancia al consumo de alcohol de acuerdo con el tipo del vehículo. - Aguilar León, Trosky Alay (2015)
Alcoholism is a disease that produces a strong need for alcohol, so that there is a physical dependency itself. Alcohol affects drivers directly in their abilities, physical, psychomotor and psychological front wheel. Alcohol consumption in our society has become a socio-cultural problem and has become the primary means of socialization. Our country ranks second on the alcohol consumption in Latin America. Driving under the influence of alcohol and repetition of this behavior has caused a serious public health problem for the Ecuadorian State. Causing traffic accidents and loss of life, unfortunately the state has not been able to prevent this behavior, caused by the misapplication of the law and the high level of corruption within the ranks of the National Police. Ecuadorian society has no culture in driver education, should be given by the State to the general population, especially in early stages in the education of children and young girls Road safety is determined by the harmonious participation of transit elements which comprise them, drivers, pedestrians, cyclists, cars and roads.